Juvenile Generalized Myasthenia Gravis: Presented as Unilateral Blepharoptosis and Successfully Managed with Pulse Intravenous Methylprednisolone - Poudel, P.; Anand, A.; Ghosh, S. (Kathmandu University Medical Journal, 2021)
Myasthenia Gravis is a rare autoimmune disorder of childhood and this is rarer in South Asia. We present a pre-pubertal 7 year old female child of seropositive Generalized Juvenile Myasthenia Gravis. She presented with unilateral blepharoptosis and later generalized symptoms appeared. Ice-pack test, Neostigmine challenge test and acetylcholine receptor antibody test were positive. Serum muscle specific tyrosine kinase antibody test was normal. She did not have thymic abnormalities. She did not respond to high dose (26 mg/kg/day) of Pyridostigmine and oral Prednisolone (2 mg/kg/day), but was successfully treated with a combination of pulse intravenous Methylprednisolone (30 mg/kg once a month for 6 months) and daily doses of oral Prednisolone (2 mg/kg/day) along with Pyridostigmine without significant side effects. This combination can be considered a potential inexpensive treatment for Juvenile Myasthenia Gravis in a resource limited area where other immunosuppressive treatments such as intravenous immunoglobulin is expensive and unaffordable.